Atomic-scale molecular models of oxidized activated carbon fibre nanoregions: Examining the effects of oxygen functionalities on wet formaldehyde adsorption. (15th September 2020) - Kowalczyk, Piotr; Gauden, Piotr A.; Wiśniewski, Marek; Terzyk, Artur P.; Furmaniak, Sylwester; Burian, Andrzej; Kaneko, Katsumi; Neimark, Alexander V.
Abstract: Construction of atomic-scale three-dimensional (3D) molecular models of unoxidized and oxidized activated carbon fiber (ACF) nanoregions is of substantial scientific and technological interest as it allows in-depth analysis of complex interfacial process. The influence of oxygen functionalities on the specific interactions with guest particles is an important factor that controls wettability, competitive adsorption of fluid mixtures, interfacial transport, reactions, or nucleation processes. We combine experimental techniques of wide-angle X-ray scattering and nitrogen adsorption porosimetry with advanced molecular modelling to construct reliable 3D molecular models of unoxidized and oxidized pitch-based ACF-5 nanoregions. ACF-5 is a ultramicroporous carbon molecular sieve with an average pore size of 0.46 ± 0.2 nm. Narrow hydrophobic nanospaces are formed between defective and slightly curved graphene-like sheets. By atomistic-scale modelling of formaldehyde adsorption at room temperature and different values of the relative humidities, we show that oxygen functionalities and water co-adsorption impact the mechanism and uptake of formaldehyde. Our simulation data indicate that hydrophobic nanopores are preferable to adsorb formaldehyde efficiently in the presence of humidity. Graphical abstract: Image 1